Formation and Transformation of Thermostable Currents by Means of Composite Unipolar and Bipolar-Unipolar Structures of Integrated Circuit - V. L. Svirid (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
Current transformers (reflectors) based on unipolar (field-effect) transistors are being studied for their effective use in integrated circuit technology. However, their widespread use is limited due to a number of features that these studies are aimed at overcoming. These features are associated not only with geometric and electrical factors, but also with temperature. Attention is drawn to composite unipolar structures, which turned out to be effective for the formation of thermostable currents. Recommendations of a circuit nature are given and the supply voltage is optimized to minimize it for the practical implementation of this mode. For the transformation of thermostable currents, original circuit solutions suitable for integral execution, based on composite bipolar-unipolar structures, were proposed and analyzed, which made it possible to change these currents both up and down without noticeable deterioration of their basic parameters.